The Notion of “Philosophy as a Way of Life”: Ambiguities and Open Questions - Eli Kramer; Marta Faustino; Hélder Telo (Eidos. A Journal for Philosophy of Culture)
Preview: Philosophy as a way of life (PWL) is an emerging field of study which in the last decades has experienced a vibrant and multifaceted development. Particularly proliferous in the areas of metaphilosophy and the history of philosophy, PWL has also been applied to a wide variety of knowledge domains beyond the academic world. Ever more prominent in contemporary debates, PWL has become a banner under which a very diversified work is being developed by scholars with originally very different areas of research and expertise, who gather under PWL by their dissatisfaction with what has become of philosophy (an abstract and purely theoretical undertaking) and their hopes about what philosophy can be (a way of thinking about and transforming one’s life). Despite the dynamic development of PWL and the wealth of literature it has inspired in recent years – or precisely because of it – there is still no consensus on what it precisely means. What exactly does this expression contain? What does it entail? To what extent is it clear and univocal? And how clear and univocal should it be?